Psychological characteristics of young handball players and its importance for handball coaches - Sosa Gonzalez, P. I.; Oliver Coronado, J. F. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
The aim of the present study was to assess a series of psychological characteristics among young Spanish handball players (under 14 and under 16), and to examine possible significant differences in these characteristics depending on sex, and age. The results obtained show that there are significant differences in most of the assessed variables, something very important to be taken into account by their coaches.